The Economic Independence of Islamic Boarding Schools From the Perspective of KH. Abdullah Syukri Zarkasyi and The Implementation with Ar-Raudlatul Hasanah Islamic Boarding School in Medan - Saputra, Jaka; Batubara, Maryam; Arif, Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The objective of this study is to examine the strategies employed by Ar-Raudlatul Hasanah Islamic boarding school in Medan in achieving economic independence and to ascertain the impact of this independence on institutional and community development. Adopting a qualitative research approach, data were gathered through in-depth interviews, observations, and document analysis, in accordance with the perspective of KH. Abdullah Syukri Zarkasyi. The primary findings indicate that Ar-Raudlatul Hasanah Islamic boarding school employs strategies, including the diversification of income sources, the establishment of business units, and the integration of internal and external resources in economic management. These economic independence measures have a positive impact on the development of pesantren facilities and the welfare of teachers and staff, while also facilitating the economic empowerment of the surrounding community through the provision of various entrepreneurship initiatives. However, a number of supporting and inhibiting factors also influence the implementation of these strategies. This study contributes to the existing literature on the economic independence of Islamic boarding schools and provides practical recommendations for other Islamic boarding schools seeking to enhance their economic independence.